Study of the Electronic Structure for Te-Doped FeSe Superconductor Prepared by Solvothermal Method - Zhao, H.-H.; Jia, X.-Y.; Shen, J.-D.; Lai, Y.-J.; Feng, L.-S.; Li, Q. (Acta Physica Polonica A, 2023)
The samples of FeSe1- xTex (x=0, 0.1, 0.2) were successfully prepared by solvothermal method. The results of X-ray diffraction show that the purity of the samples prepared by the solvothermal method is higher than that of the samples prepared by the solid-state reaction and flux method. The superconducting transition temperature (Tc) of FeSe1-xTex for x=0, 0.1, 0.2 samples is near 9.3 K, 12.4 K, and 13.9 K, respectively, which is a bit higher than that of bulk samples. The electronic structures of these samples are investigated by X-ray photoemission spectroscopy and X-ray absorption spectroscopy. The Fe 2p X-ray photoemission spectroscopy spectra shift to higher binding energy by Te doping due to the increase in hole densities. X-ray photoemission spectroscopy spectra of Se 3d and Te 3d shift to higher binding energy and lower binding energy, respectively, resulting from the charge transfer between Se and Te. It is suggested that the hybridization between Fe 3d and Se 4p is strengthened. Our results imply that the hybridization between Fe 3d and Se 4p probably plays an important role in superconductivity.